Analisis Promosi Layanan Bookless di Perpustakaan IAIN Purwokerto - Indah Wijaya Antasari (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Library promotion is a must for the information marketing. Even more if the library has new service such as bookless library service in the library of IAIN Purwokerto. This research uses qualitative research aproach, and the data accumulating tecnique is by using observation, interview and documentation. The result of this research is there are so many users who didn’t know about bookless library service in IAIN Purwokerto. It can be concluded that promotion media of library services should be using various kind of promtion media. after the user got the explanation, they knew and agreed that the bookless service in the library is useful in helping their study in IAIN purwokerto, and this user perception got apreciation from the head of IAIN Purwokerto Library. Users sugested that the promotion media that will be used, such as; broadside of bookless service user manual, throuh the explanation about the importance of bookless service from student cordinators to every class room, and more guidance banners in the library. This research needs the subsequence studies to develop the other media and it’s evaluation.